Żywienie młodzieży akademickiej – wybrane uwarunkowania = Nutrition of university students – selected determinants - Kowalczyk, Anna; Kozłowska, Ewelina; Kalinowski, Paweł; Podstawka, Danuta; Makara Studzińska, Marta (Journal of Education, Health and Sport, 2015)
Kowalczyk Anna, Kozłowska Ewelina, Kalinowski Paweł, Podstawka Danuta, Makara Studzińska Marta. Żywienie młodzieży akademickiej – wybrane uwarunkowania = Nutrition of university students – selected determinants. Journal of Education, Health and Sport. 2015;5(9):515-526. ISSN 2391-8306. DOI10.5281/zenodo.31460 http://dx.doi.org/10.5281/zenodo.31460 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A515-526 https://pbn.nauka.gov.pl/works/634608 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 26.08.2015. Revised 05.09.2015. Accepted: 22.09.2015. Żywienie młodzieży akademickiej – wybrane uwarunkowania Nutrition of university students – selected determinants Anna Kowalczyk1, Ewelina Kozłowska2, Paweł Kalinowski2, Danuta Podstawka3, Marta Makara Studzińska3 1.Studenckie Koło Naukowe Badań Nad Jakością Życia działające przy Zakładzie Psychologii Stosowanej Uniwersytetu Medycznego w Lublinie 2.Samodzielna Pracownia Epidemiologii, Uniwersytet Medyczny w Lublinie 3.Zakład Psychologii Stosowanej, Uniwersytet Medyczny w Lublinie Autor do korespondencji / Author for correspondence lic. Anna Kowalczyk e-mail: annakowalczyklublin@gmail.com Streszczenie Wstęp. Każdy z okresów życia człowieka warunkuje jego późniejszy stan zdrowia. Podjęcie studiów rozpoczyna nowy etap w życiu młodego człowieka. Kształtowane w rodzinie zachowania i postawy względem zdrowia, w środowisku akademickim mogą ulegać zmianom lub też utrwalać się. Celem pracy jest określenie wybranych determinant warunkujących prawidłowe żywienie młodzieży akademickiej. Materiał i metoda. W roku akademickim 2013/2014 przeprowadzono sondaż diagnostyczny za pomocą techniki ankietowania. Narzędzie stanowił autorski kwestionariusz ankiety. Badanie przeprowadzono wśród 100 osobowej grupy studentów Uniwersytetu Medycznego w Lublinie. Wyniki. Za główną determinantę prawidłowego odżywiania się studenci uznali ilość wolnego czasu między zajęciami (41%). W dalszej kolejności wskazywano na takie czynniki jak: odległość miejsca zamieszkania od uczelni (18%), dostępność do uczelnianej stołówki (10%), bliskie sąsiedztwo uczelni z lokalami gastronomicznymi (9%) czy też status materialny studenta (9%). Mało znaczącymi czynnikami okazały się: umiejętność gospodarowania środkami pieniężnymi (5%) oraz zaopatrzenie sklepików w sąsiedztwie uczelni (4%). Niepokojący jest fakt, iż 48% studentów regularnie bądź sporadycznie rezygnuje z posiłku by w ten sposób zaoszczędzić pieniądze na inne cele. Wnioski. Należy stworzyć studentom właściwe warunki do spożywania posiłków o odpowiedniej jakości i w odpowiednich odstępach czasu. Właściwe rozplanowanie zajęć w ciągu dnia, zaopatrywanie się w produkty spożywcze przed rozpoczęciem zajęć oraz dostępność do placówek gastronomicznych może znacząco poprawić sposób żywienia młodzieży akademickiej. Słowa kluczowe: żywienie, młodzież akademicka, uwarunkowania. Abstract Introduction. Each of human life periods is a condition for its later health. Undertaking studies is a beginning of new life stage of a young man. Developed behaviors in the family and attitudes with regard to health, in the university environment may undergo changes or become established. An aim of this work is to determine selected determinants conditioning proper nutrition of university students. Material and method. Diagnostic survey was conducted in the academic year 2013/2014 using survey technique. An author’s questionnaire form constituted the tool. Study was carried out on a sample of one hundred students of the Medical University in Lublin. Results. Students regarded the amount of free time between classes as the main determinant of proper nutrition (41%). Later they indicated such factors as: distance to the place of residence from the university (18%), availability to the university canteen (10%), immediate neighborhood of the university with dining (9%), or student’s material status (9%). Less significant factors turned out to be: ability of cash management (5%) and supply of shops in the university vicinity (4%). Concern is that 48% of students regularly or occasionally abandon the meal in order to save money for other purposes. Conclusions. It is necessary to create appropriate nutrition conditions for students with adequate quality and in appropriate time intervals. Proper layout of classes during the day, supply with food products before beginning the classes and availability to catering facilities may significantly improve dietary of university students. Keywords: nutrition, university students, determinants.